Poverty, Growth and Inequality in Developing Countries - Housseima, Guiga; Ben Rejeb, Jaleleddine (International Journal of Economics and Financial Issues, 2012)
The purpose of this paper is to assess the position of some developing countries in relation to different theories about the relationship between poverty, growth and inequality. We conducted an econometric analysis through a study using panel data from 52 developing countries over the period 1990-2005, to determine the main sources of poverty reduction and show the interdependence between poverty, inequality and growth by using a system of simultaneous equations. This method is rarely applied econometric panel data and especially in the case studies on poverty. Our results indicate that the state investment in social sectors such as education and health and improving the living conditions of the rural population can promote economic growth and reducing inequality. Therefore, the Kuznets hypothesis is based on a relationship between economic growths to income inequality is most appropriate. Keywords: Poverty, Growth; Inequality; Panel Data; Simultaneous System Equations. JEL Classifications: C30; C33; I32; O15